Potential Interaction of Pinocembrin with Drug Transporters and Hepatic Drug-Metabolizing Enzymes - Sirima Sangkapat; Rattiporn Boonnop; Jeerawat Pimta; Napason Chabang; Bodee Nutho; Promsuk Jutabha; Sunhapas Soodvilai (Pharmaceuticals)
Background/Objectives: Pinocembrin is a promising drug candidate for treating ischemic stroke. The interaction of pinocembrin with drug transporters and drug-metabolizing enzymes is not fully revealed. The present study aims to evaluate the interaction potential of pinocembrin with cytochrome P450 (CYP450: CYP2B6, CYP2C9, and CYP2C19) and drug transporters including organic anion transporters (OAT1 and OAT3), organic cation transporters (OCT1 and OCT2), multidrug and toxin extrusion (MATE1 and MATE2, P-glycoprotein (P-gp), and breast cancer resistance protein (BCRP). Methods: The interactions of pinocembrin on drug transporters were determined in the Madin–Darby canine kidney (MDCK) cells overexpressing human (h)OAT1 or hOAT3 and in the Chinese hamster ovary (CHO-K1) cells overexpressing hOCT1, hOCT2, hMATE1, or hMATE2. The interactions of pinocembrin with BCRP and P-glycoprotein were determined in Caco-2 cells. The CYP450 enzyme inhibitory activity was assessed by a cell-free CYP450 screening assay. Results: Pinocembrin effectively inhibited the function of OAT1 and OAT3 with a half-inhibitory concentration (IC50) and inhibitory constant (Ki) of ∼2 μM. In addition, it attenuated the toxicity of tenofovir, a substrate of hOAT1, in cells overexpressing hOAT1. Based on the kinetic study and molecular docking, pinocembrin inhibited OAT1 and OAT3 via a competitive inhibition. In contrast to hOAT1 and hOAT3, pinocembrin did not significantly inhibit the function of OCT1, OCT2, MATE1, MATE2, BCRP, and P-glycoprotein. In addition, pinocembrin potently inhibited the activity of CYP2C19, whereas it exhibited low inhibitory potency on CYP2B6 and CYP2C9. Conclusions: The present study reveals the potential drug interaction of pinocembrin on OAT1, OAT3, and CYP2C19. Co-administration with pinocembrin might affect OAT1-, OAT3-, and CYP2C19-mediated drug pharmacokinetic profiles.